Positive electrode material, preparation method thereof and zinc ion battery
By embedding the conductive metal organic frame Cu-BTA in the positive electrode material of the zinc ion battery, the problem of pre-embedded cation removal is solved, the rate performance and cycle stability of the zinc ion battery are improved, and high capacity and excellent energy storage characteristics are achieved.
Patent Information
- Application Number
- CN202411389769.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing zinc ion battery positive electrode materials have reduced the specific capacity of the battery during the zinc ion embedding and detachment process, and poor circulation performance.
Cu-BTA is embedded in the layered structure of vanadium oxide by using conductive metal organic frame Cu-BTA, and nanosheet-shaped positive electrode material is prepared through hydrothermal reaction, and the insertion amount of Cu-BTA is controlled to be within the range of 0.10≤x≤0.30 to form a continuous chain structure. To improve ionic conductivity and rate performance.
The migration path of zinc ions is improved, electron transfer is promoted, the rate performance and cycle stability of the battery are enhanced, and part of the capacity is provided to participate in zinc storage, which improves electrochemical performance.
Smart Images

Figure CN119230784A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a positive electrode material and a preparation method thereof, and a zinc ion battery. Background Art
[0002] At present, benefiting from the low cost, high safety, environmental friendliness, high energy density and high power density of zinc metal negative electrode, rechargeable aqueous zinc-ion batteries have received extensive attention and are considered to be one of the most attractive alternatives to lithium-ion batteries. The electrochemical performance of aqueous zinc-ion batteries mainly depends on the positive electrode material. Although the ionic radius of zinc ions is relatively small, the divalent nature of zinc ions causes strong electrostatic interactions with the host lattice, resulting in hindered zinc ion embedding and slow diffusion kinetics. Among the positive electrode materials for zinc-ion batteries currently being developed, vanadium oxide can achieve multi-electron transfer in electrode materials due to its variable valence state from +2 to +5, thereby achieving high capacity; in addition, the interlayer spacing of vanadium oxide is adjustable and the reserves of vanadium oxide are abundant, so it is considered to be a promising positive electrode material for zinc-ion batteries.
[0003] Although the pre-embedded cations can expand the lattice spacing and accelerate ion diffusion, the electrochemical stability of the main material is still affected by structural degradation, especially during the repeated embedding or extraction of zinc ions. Due to the weak interaction between the hydrated pre-embedded cations and the oxygen from the main layer, the pre-embedded cations will gradually extract with the change of the vanadium valence state, resulting in a decrease in the battery specific capacity. Therefore, how to provide a positive electrode material to avoid the extraction of pre-embedded cations is an urgent problem to be solved. Summary of the invention
[0004] The present invention provides a positive electrode material and a preparation method thereof, and a zinc ion battery, aiming to solve the problem that pre-embedded cations gradually escape with the change of vanadium valence state.
[0005] To solve the above problems, the present invention provides a positive electrode material, including a conductive metal organic framework and vanadium oxide; the conductive metal organic framework is embedded between the layered structures of vanadium oxide; the chemical formula of the positive electrode material is (Cu-BTA) x V 2 O 5 ; Among them, 0.10≤x≤0.30, BTA is 1,2,4,5-benzenetetramine, and Cu-BTA is a conductive metal organic framework.
[0006] The positive electrode material provided by the present invention comprises a conductive metal organic framework and vanadium oxide. By embedding the conductive metal organic framework between the layered structures of vanadium oxide, on the one hand, the conductive metal organic framework can expand the interlayer distance of vanadium oxide, improve the electronic or ionic conductivity of the electrode material, promote the electron transfer in the material and the migration dynamics of zinc ions between vanadium oxide layers, so that the battery has excellent rate performance; on the other hand, the conductive metal organic framework itself is relatively large, the interlayer migration steric hindrance is relatively large, and the conductive metal organic framework is electrically neutral and will not leave the interlayer with zinc ions under electrochemical action, so that the battery has excellent cycle performance; in addition, the embedded conductive metal organic framework itself can also participate in zinc storage and can provide partial capacity.
[0007] The chemical formula of the positive electrode material is (Cu-BTA) x V 2 O 5 , wherein 0.10≤x≤0.30, the conductive metal organic framework is embedded in the vanadium oxide material. If the amount of the conductive metal organic framework inserted is too small, the electronic conductivity between the layers will be poor and the rate performance of the battery will be poor; if the amount of the conductive metal organic framework inserted is too much, the capacity will be reduced. The inventor speculates that it may be because the amount of the conductive metal organic framework inserted is too small, the conductive metal organic framework between the vanadium oxide layers cannot form a continuous chain structure, and the amount of the conductive metal organic framework inserted is too much, which hinders the migration of zinc ions between the layers. The proportion of the Cu-BTA conductive metal organic framework is controlled to 0.10≤x≤0.30. The appropriate proportion range can provide partial capacity to participate in zinc storage while ensuring the higher ionic conductivity of the positive electrode material and the excellent rate performance of the battery.
[0008] In any of the above technical solutions, the structure of the positive electrode material is in the form of nanosheets, the length of the nanosheets is 80nm-200nm, and the thickness of the nanosheets is 3nm-7nm.
[0009] The cathode material composed of a conductive metal organic framework and vanadium oxide has a nanosheet structure, which can effectively shorten the migration path of zinc ions and promote the rapid storage of zinc ions. It also promotes the rapid transfer of electrons and has a faster electrochemical reaction kinetics process, which makes the cathode material have a higher capacity, good rate performance and cycle stability. The nanosheet structure of the cathode material promotes the rapid embedding or extraction process of zinc ions, showing excellent energy storage characteristics, which generally helps to improve (Cu-BTA) x V 2 O 5 Electrochemical properties of cathode materials.
[0010] In any of the above technical solutions, the interlayer spacing of the vanadium oxide is 1.30nm-1.45nm.
[0011] The appropriate vanadium oxide interlayer spacing can reduce the Zn 2+ The transmission between the vanadium oxide layers is hindered, thereby improving the rate performance and avoiding the vanadium oxide structure in the Zn 2+ Collapse occurs during repeated insertion / extraction, improving cycle stability.
[0012] The present invention also provides a method for preparing a positive electrode material, the method for preparing the positive electrode material as described above, the method comprising the following steps: S10: dispersing and dissolving vanadium pentoxide, hydrogen peroxide, copper nitrate trihydrate and water in a mass ratio of 1: (4-6): (0.13-0.40): (80-120), and then performing a hydrothermal reaction to obtain copper vanadate; S20: dispersing copper vanadate in water to form a copper vanadate dispersion, adding a 1,2,4,5-benzenetetramine tetrahydrochloride solution to the copper vanadate dispersion, and then adding an ammonia solution thereto and stirring to react; the mass ratio of 1,2,4,5-benzenetetramine tetrahydrochloride in the 1,2,4,5-benzenetetramine tetrahydrochloride solution, copper vanadate in the copper vanadate dispersion, and an ammonia source in the ammonia solution is 1: (2.70-6.63): (0.15-0.25); and obtaining the positive electrode material.
[0013] The preparation method for preparing positive electrode materials provided by the present invention has relatively mild process conditions, low energy consumption, abundant material sources, and good application and industrialization prospects. Among them, the hydrothermal reaction in the first step is compared with other powder preparation methods. The powder obtained by the hydrothermal reaction has the characteristics of complete grain development, small particle size, and uniform distribution, which makes the final positive electrode material a uniform flaky structure. Vanadium pentoxide, hydrogen peroxide and copper nitrate trihydrate are dispersed and dissolved in water to ensure that the three can be mixed evenly. The purpose of adding hydrogen peroxide is to dissolve the vanadium pentoxide so that the vanadium pentoxide exists in the mixed solution in the form of ions, thereby opening the interlayer spacing of vanadium oxide so that in the subsequent hydrothermal reaction process, Cu 2+ Enter the vanadium oxide interlayer.
[0014] The 1,2,4,5-benzenetetraamine tetrahydrochloride solution reacts with the copper vanadate obtained by S10. The copper vanadate provides copper ions and the 1,2,4,5-benzenetetraamine tetrahydrochloride provides BTA molecules. After the two are combined, a Cu-BTA conductive metal organic framework can be obtained and embedded in the vanadium oxide material. The addition of an ammonia solution can deprotonate the 1,2,4,5-benzenetetraamine tetrahydrochloride, thereby reacting with the Cu between the vanadium oxide layers. 2+Coordination was performed to obtain a positive electrode material with a Cu-BTA conductive metal organic framework. The Cu-BTA conductive metal organic framework is embedded in the vanadium oxide with a layered structure. On the one hand, its steric hindrance is large, and it is not easy to move between layers, and it prevents copper ions from leaving the interlayer as the charge and discharge cycle proceeds, thereby improving the cycle stability; on the other hand, Cu-BTA itself can provide zinc storage sites, thereby increasing the capacity; furthermore, Cu-BTA itself is a conductive metal organic framework, which can improve the conductivity of the positive electrode material, thereby facilitating the improvement of rate performance.
[0015] By controlling the mass ratio of vanadium pentoxide and copper nitrate trihydrate, it is ensured that a positive electrode material having a Cu-BTA conductive metal organic framework can be finally synthesized. 2+ The initial content determines the amount of Cu-BTA conductive metal organic framework inserted after synthesis. If the amount of copper nitrate trihydrate reacted is too small, the amount of vanadium oxide inserted into the Cu-BTA conductive metal organic framework is too small, so that the interlayer Cu-BTA cannot form a continuous chain structure, which leads to poor interlayer electronic conductivity and poor rate performance. If the amount of copper nitrate trihydrate reacted is too much, the amount of vanadium oxide inserted into the Cu-BTA conductive metal organic framework is too large, which will hinder the migration of zinc ions between layers and cause capacity reduction. The appropriate mass ratio of vanadium pentoxide and copper nitrate trihydrate can ensure the high ionic conductivity of the positive electrode material and the excellent rate performance of the battery, while also providing part of the capacity to participate in zinc storage.
[0016] By controlling the mass ratio of 1,2,4,5-benzenetetramine tetrahydrochloride and copper vanadate, it is ensured that the positive electrode material with Cu-BTA conductive metal organic framework can be finally synthesized. If the amount of copper vanadate reacted is too small, the amount of vanadium oxide inserted into the Cu-BTA conductive metal organic framework is too small, so that the interlayer Cu-BTA cannot form a continuous chain structure, which leads to poor interlayer electronic conductivity and poor rate performance. If the amount of copper vanadate reacted is too large, the amount of vanadium oxide inserted into the Cu-BTA conductive metal organic framework is too large, which will hinder the migration of zinc ions between layers and cause a decrease in capacity. By controlling the appropriate mass ratio of 1,2,4,5-benzenetetramine tetrahydrochloride and copper vanadate, the interlayer Cu-BTA forms a continuous chain structure, improves the electronic conductivity and rate performance of the positive electrode material, and avoids the insertion of vanadium oxide into the Cu-BTA conductive metal organic framework to hinder the migration of zinc ions between layers, taking into account the capacity of the positive electrode material.
[0017] In any of the above technical solutions, S10 specifically includes: S11: dispersing and dissolving vanadium pentoxide, hydrogen peroxide and copper nitrate trihydrate in water to obtain a mixed solution; S12: after stirring the mixed solution evenly, transferring it to a reactor for hydrothermal reaction to obtain a first reaction product; S13: naturally cooling the first reaction product to room temperature, and sequentially performing precipitation centrifugal washing and vacuum drying to obtain copper vanadate.
[0018] The method comprises dispersing and dissolving vanadium pentoxide, hydrogen peroxide and copper nitrate trihydrate in water to ensure that the three are evenly mixed; stirring the mixed solution to ensure that the mixed solution is stirred more evenly and improve the subsequent reaction efficiency; and performing a hydrothermal reaction on the mixed solution in a reactor to obtain a first reaction product. The reaction method has the characteristics of simple operation, low cost and excellent performance of the synthesized nanocrystals. The first reaction product is cooled to room temperature to obtain a crystalline substance, and then centrifugal washing and vacuum drying are performed in sequence to remove impurities on the surface of the crystal, and finally copper vanadate is obtained.
[0019] In any of the above technical solutions, in S12, the temperature of the hydrothermal reaction is ≥150°C; and / or the time of the hydrothermal reaction is 12h-96h.
[0020] The appropriate hydrothermal reaction temperature can ensure that Cu 2+ All of them enter the vanadium oxide interlayer to form Cu-BTA molecules, and then Cu-BTA provides support for the interlayer, thereby improving the rate performance and cycle performance; the evenly stirred mixed solution is placed in a reactor for hydrothermal reaction, and the hydrothermal reaction time is controlled within 12h-96h to ensure that the mixed solution reacts more fully.
[0021] In any of the above technical solutions, the stirring time is 10min-60min; and / or the temperature of the hydrothermal reaction is 200℃-250℃; and / or the cleaning solvent for the precipitation centrifugal cleaning includes deionized water and anhydrous ethanol; and / or the temperature of vacuum drying is 60℃-100℃; and / or the time of vacuum drying is 3h-48h.
[0022] The mixed solution is stirred at 25°C-60°C, and the stirring time is controlled within 10min-60min to promote more uniform stirring of the mixed solution, which is convenient for the subsequent hydrothermal reaction; the uniformly stirred mixed solution is placed in a reactor for hydrothermal reaction, and the temperature of the hydrothermal reaction is controlled within 200°C-250°C. The appropriate hydrothermal reaction temperature can promote the Cu 2+All of them enter the vanadium oxide interlayer to form Cu-BTA molecules, and then Cu-BTA provides support for the interlayer, thereby improving the rate performance and cycle performance; the cleaning solvents for the precipitation centrifugal cleaning include deionized water and anhydrous ethanol, and each is centrifuged for 3 times; when the first reaction product is cleaned, it is vacuum dried, the vacuum drying temperature is 60℃-100℃, and the vacuum drying time is 3h-48h, and finally the required copper vanadate is obtained.
[0023] In any of the above technical schemes, S20 specifically includes: S21: dissolving 1,2,4,5-benzenetetraamine tetrahydrochloride in water to obtain a 1,2,4,5-benzenetetraamine tetrahydrochloride solution; S22: adding the 1,2,4,5-benzenetetraamine tetrahydrochloride solution to the copper vanadate dispersion under stirring conditions, adding an ammonia solution thereto after stirring evenly, and then transferring it to a constant temperature water bath and stirring for reaction to obtain a second reaction product; S23: centrifugally cleaning and vacuum drying the second reaction product in sequence to obtain a positive electrode material.
[0024] Dissolving 1,2,4,5-benzenetetraamine tetrahydrochloride in water can promote its reaction with the copper vanadate dispersion and make the reaction more complete; stirring the reaction in a constant temperature water bath can not only make the reaction more uniform, but also ensure the stability of heating, which is conducive to the reaction; the second reaction product is centrifugally cleaned and vacuum dried in turn to remove impurities on the crystal surface, and finally obtain the positive electrode material.
[0025] In any of the above technical solutions, the stirring speed is 100r / min-400r / min; and / or the reaction time is 3h-48h; and / or the cleaning solvent for centrifugal cleaning includes deionized water and acetone; and / or the vacuum drying temperature is 60℃-100℃; and / or the vacuum drying time is 12h-96h.
[0026] The reactants are placed in a constant temperature water bath and stirred for reaction, and the stirring speed is controlled to be 100r / min-400r / min. By controlling the appropriate stirring speed, the diffusion of BTA molecules into the interlayer of vanadium oxide is promoted to improve the rate performance and cycle performance of the positive electrode material. The reaction time of 1,2,4,5-benzenetetraamine tetrahydrochloride and copper vanadate is controlled to be 3h-48h to ensure a more complete reaction; the cleaning solvents for centrifugal cleaning include deionized water and acetone, and each is centrifuged for 3 times; after the second reaction product is cleaned, it needs to be vacuum dried, the vacuum drying temperature is 60℃-100℃, and the vacuum drying time is 12h-96h, and finally the desired positive electrode material is obtained.
[0027] The present invention also provides a zinc ion battery, comprising the positive electrode material as described above. The zinc ion battery has the same beneficial effects as the positive electrode material as described above, so it will not be described in detail here.
[0028] After adopting the technical solution of the present invention, the following technical effects can be achieved: (1) The conductive metal organic framework in the positive electrode material provided by the present invention can expand the interlayer spacing of vanadium oxide, improve the electronic or ionic conductivity of the electrode material, promote the electron transfer in the material and the migration kinetics of zinc ions between vanadium oxide layers, so that the battery has excellent rate performance; (2) The conductive metal organic framework itself is relatively large, and the interlayer migration steric hindrance is relatively large. In addition, the conductive metal organic framework is electrically neutral and will not leave the interlayer with the zinc ions under electrochemical action, which makes the battery have excellent cycle performance; (3) The embedded conductive metal-organic framework itself can also participate in zinc storage and provide part of the capacity; (4) The positive electrode material of the present invention has a nanosheet structure, which makes the migration path of zinc ions shorter. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 This is an electron microscope image of the positive electrode material provided in Example 1 of the present invention; Figure 2 The XRD diffraction pattern provided by Example 1 of the present invention; Figure 3 The XRD diffraction pattern provided for Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Among various energy storage systems, lithium-ion batteries with high energy density and long cycle life dominate the market of portable electronic products. However, limited lithium resources, high cost, complex manufacturing processes and safety hazards caused by flammable organic electrolytes have prompted researchers to design other alternative energy storage batteries. Among them, rechargeable aqueous zinc-ion batteries have received widespread attention due to the low cost, high safety, environmental friendliness, high energy density and high power density of zinc metal negative electrodes, and are considered to be one of the most attractive alternatives to lithium-ion batteries.
[0032] At present, the electrochemical performance of aqueous zinc-ion batteries mainly depends on the positive electrode material. Although the ionic radius of zinc ions is relatively small, the divalent nature of zinc ions causes strong electrostatic interactions with the host lattice, resulting in hindered zinc ion embedding and slow diffusion kinetics. Therefore, it is critical to find a suitable positive electrode with excellent electrochemical performance. Among the zinc-ion battery positive electrode materials currently developed, vanadium oxide can achieve multi-electron transfer in the electrode material due to its variable valence state from +2 to +5, thereby achieving high capacity. In addition, the interlayer spacing of vanadium oxide is adjustable, and vanadium oxide reserves are abundant, so it is considered to be a promising zinc-ion battery positive electrode material. However, vanadium oxides, such as V 2 O 5 , and its interlayer spacing is small. Although the interlayer spacing can be increased by pre-embedded metal ions, its structure is still unstable during the cycle, which ultimately leads to poor cycle performance.
[0033] Although pre-embedded cations can expand the lattice spacing and accelerate ion diffusion, the electrochemical stability of the main material is still affected by structural degradation, especially during the repeated embedding or extraction of zinc ions. Since the interaction between the hydrated pre-embedded cations and the oxygen from the main layer is weak, the pre-embedded cations will gradually extract with the change of the vanadium valence state, resulting in a decrease in the battery specific capacity and reduced cycle performance.
[0034] Conductive metal organic frameworks are composed of transition metal ions and π-conjugated organic ligands. The d orbitals of transition metal ions and the π orbitals of organic ligands will hybridize, thereby promoting electron delocalization, thereby improving the charged state of the material and increasing the conductivity of the material. 2+ The Cu-BTA conductive metal organic framework composed of 1,2,4,5-benzenetetramine (BTA) has high porosity, high crystallinity, good thermal stability and chemical stability, and can store zinc itself. In addition, the preparation process of the conductive metal organic framework is simple and the preparation conditions are mild.
[0035] The embodiment of the present invention provides a positive electrode material, comprising a conductive metal organic framework and vanadium oxide; the conductive metal organic framework is embedded between the layered structures of vanadium oxide; the chemical formula of the positive electrode material is (Cu-BTA) x V 2 O 5 ; Among them, 0.10≤x≤0.30, BTA is 1,2,4,5-benzenetetramine, and Cu-BTA is a conductive metal organic framework.
[0036] The positive electrode material provided by the present invention comprises a conductive metal organic framework and vanadium oxide. By embedding the conductive metal organic framework between the layered structures of vanadium oxide, on the one hand, the conductive metal organic framework can expand the interlayer distance of vanadium oxide, improve the electronic or ionic conductivity of the electrode material, promote the electron transfer in the material and the migration dynamics of zinc ions between vanadium oxide layers, so that the battery has excellent rate performance; on the other hand, the conductive metal organic framework itself is relatively large, the interlayer migration steric hindrance is relatively large, and the conductive metal organic framework is electrically neutral and will not leave the interlayer with zinc ions under electrochemical action, so that the battery has excellent cycle performance; in addition, the embedded conductive metal organic framework itself can also participate in zinc storage and can provide partial capacity.
[0037] Among the components of the positive electrode material, Cu-BTA is a conductive metal organic framework, which itself has zinc storage sites. In addition to the CN bonds or C=N bonds in BTA participating in zinc storage through bond breaking and rearrangement, the central metal ion Cu 2+ Redox reactions also occur to participate in zinc storage, and the Cu-BTA conductive metal-organic framework can enable vanadium oxide materials to have higher capacity.
[0038] Furthermore, the chemical formula of the positive electrode material is (Cu-BTA) x V 2 O 5 , wherein 0.10≤x≤0.30, the conductive metal organic framework is inserted into the vanadium oxide material. If the amount of the conductive metal organic framework inserted is too small, the interlayer electronic conductivity will be poor and the rate performance of the battery will be poor; if the amount of the conductive metal organic framework inserted is too much, the capacity will be reduced. The inventor speculates that it may be because the amount of the conductive metal organic framework inserted is too small, the conductive metal organic framework between the vanadium oxide layers cannot form a continuous chain structure, and the amount of the conductive metal organic framework inserted is too much, which hinders the migration of zinc ions between layers. The proportion of the Cu-BTA conductive metal organic framework is controlled to 0.10≤x≤0.30. The appropriate proportion range can provide partial capacity to participate in zinc storage while ensuring the higher ionic conductivity of the positive electrode material and the excellent rate performance of the battery. Preferably, the proportion of the Cu-BTA conductive metal organic framework is controlled to 0.15≤x≤0.25.
[0039] In some embodiments of the present application, the structure of the positive electrode material is in the form of nanosheets, the length of the nanosheets is 80nm-200nm, and the thickness of the nanosheets is 3nm-7nm.
[0040] like Figure 1As shown in the figure, the cathode material composed of a conductive metal organic framework and vanadium oxide has a nanosheet structure, which can effectively shorten the migration path of zinc ions and promote the rapid storage of zinc ions. It also promotes the rapid transfer of electrons and has a faster electrochemical reaction kinetics process, so that the cathode material has a higher capacity, good rate performance and cycle stability. The nanosheet structure of the cathode material promotes the rapid insertion or extraction of zinc ions, showing excellent energy storage characteristics, which generally helps to improve (Cu-BTA) x V 2 O 5 Electrochemical properties of cathode materials.
[0041] In some embodiments of the present application, the interlayer spacing of the vanadium oxide is 1.30 nm-1.45 nm.
[0042] The appropriate vanadium oxide interlayer spacing can reduce the Zn 2+ The transmission between the vanadium oxide layers is hindered, thereby improving the rate performance and avoiding the vanadium oxide structure in the Zn 2+ Collapse occurs during repeated insertion / extraction, improving cycle stability.
[0043] An embodiment of the present invention also provides a method for preparing a positive electrode material, the preparation method is used to prepare the positive electrode material as described above, and the preparation method comprises the following steps: S10: dispersing and dissolving vanadium pentoxide, hydrogen peroxide, copper nitrate trihydrate and water in a mass ratio of 1: (4-6): (0.13-0.40): (80-120), and then performing a hydrothermal reaction to obtain copper vanadate; S20: dispersing copper vanadate in water to form a copper vanadate dispersion, adding a 1,2,4,5-benzenetetramine tetrahydrochloride solution to the copper vanadate dispersion, and then adding an ammonia solution thereto and stirring to react; the mass ratio of 1,2,4,5-benzenetetramine tetrahydrochloride in the 1,2,4,5-benzenetetramine tetrahydrochloride solution, copper vanadate in the copper vanadate dispersion, and an ammonia source in the ammonia solution is 1: (2.70-6.63): (0.15-0.25); and obtaining a positive electrode material.
[0044] Preferably, the mass ratio of vanadium pentoxide, hydrogen peroxide, copper nitrate trihydrate and water is 1:4.44:(0.20-0.32):(90-110).
[0045] Preferably, the mass ratio of 1,2,4,5-benzenetetraamine tetrahydrochloride, copper vanadate and the ammonia source in a 28 wt.% ammonia solution is 1:(3.50-5.83):0.17.
[0046] The preparation method for preparing positive electrode materials provided by the present invention comprises the following steps: firstly, vanadium pentoxide, hydrogen peroxide and copper nitrate trihydrate are subjected to a hydrothermal reaction to generate copper vanadate, and then copper vanadate, 1,2,4,5-benzenetetraamine tetrahydrochloride solution and ammonia solution are reacted again to generate a positive electrode material. The process conditions are relatively mild, the energy consumption is low, the material source is abundant, and there is a good prospect for application and industrialization. Among them, the powder obtained by the hydrothermal reaction in the first step has the characteristics of complete grain development, small particle size and uniform distribution compared with other powder preparation methods, which makes the final positive electrode material a uniform flaky structure. By dispersing and dissolving vanadium pentoxide, hydrogen peroxide and copper nitrate trihydrate in water, it is ensured that the three can be mixed evenly, wherein the purpose of adding hydrogen peroxide is to dissolve vanadium pentoxide so that vanadium pentoxide exists in the mixed solution in the form of ions, thereby being able to open the interlayer spacing of vanadium oxide, so that in the subsequent hydrothermal reaction process, Cu 2+ Enter the vanadium oxide interlayer.
[0047] Among them, in S20, 1,2,4,5-benzenetetraamine tetrahydrochloride solution is reacted with copper vanadate obtained in S10. Copper vanadate provides copper ions, and 1,2,4,5-benzenetetraamine tetrahydrochloride provides BTA molecules. After the two are combined, a Cu-BTA conductive metal organic framework can be obtained and embedded in the vanadium oxide material. The addition of ammonia solution can deprotonate 1,2,4,5-benzenetetraamine tetrahydrochloride, thereby reacting with the Cu between the vanadium oxide layers. 2+ Coordination was performed to obtain a positive electrode material having a Cu-BTA conductive metal organic framework. The Cu-BTA conductive metal organic framework is embedded in vanadium oxide with a layered structure. Compared with Cu 2+ As for ions, on the one hand, its steric hindrance is large, and it is not easy to move between layers, and it prevents copper ions from leaving the interlayer during the charge and discharge cycle, thereby improving the cycle stability; on the other hand, Cu-BTA itself can provide zinc storage sites, thereby increasing the capacity; furthermore, Cu-BTA itself is a conductive metal organic framework, which can improve the conductivity of the positive electrode material, thereby facilitating the improvement of the rate performance.
[0048] By controlling the mass ratio of vanadium pentoxide and copper nitrate trihydrate, it is ensured that a positive electrode material having a Cu-BTA conductive metal organic framework can be finally synthesized. 2+The initial content determines the amount of Cu-BTA conductive metal organic framework inserted after synthesis. If the amount of copper nitrate trihydrate reacted is too small, the amount of vanadium oxide inserted into the Cu-BTA conductive metal organic framework is too small, so that the interlayer Cu-BTA cannot form a continuous chain structure, which leads to poor interlayer electronic conductivity and poor rate performance. If the amount of copper nitrate trihydrate reacted is too much, the amount of vanadium oxide inserted into the Cu-BTA conductive metal organic framework is too large, which will hinder the migration of zinc ions between layers and cause capacity reduction. The appropriate mass ratio of vanadium pentoxide and copper nitrate trihydrate can ensure the high ionic conductivity of the positive electrode material and the excellent rate performance of the battery, while also providing part of the capacity to participate in zinc storage.
[0049] By controlling the mass ratio of 1,2,4,5-benzenetetramine tetrahydrochloride and copper vanadate, it is ensured that the positive electrode material with Cu-BTA conductive metal organic framework can be finally synthesized. If the amount of copper vanadate reacted is too small, the amount of vanadium oxide inserted into the Cu-BTA conductive metal organic framework is too small, so that the interlayer Cu-BTA cannot form a continuous chain structure, which leads to poor interlayer electronic conductivity and poor rate performance. If the amount of copper vanadate reacted is too large, the amount of vanadium oxide inserted into the Cu-BTA conductive metal organic framework is too large, which will hinder the migration of zinc ions between layers and cause a decrease in capacity. By controlling the appropriate mass ratio of 1,2,4,5-benzenetetramine tetrahydrochloride and copper vanadate, the interlayer Cu-BTA forms a continuous chain structure, improves the electronic conductivity and rate performance of the positive electrode material, and avoids the insertion of vanadium oxide into the Cu-BTA conductive metal organic framework to hinder the migration of zinc ions between layers, taking into account the capacity of the positive electrode material.
[0050] In some embodiments of the present application, S10 specifically includes: S11: dispersing and dissolving vanadium pentoxide, hydrogen peroxide and copper nitrate trihydrate in water to obtain a mixed solution; S12: after stirring the mixed solution evenly, transferring it to a reactor for hydrothermal reaction to obtain a first reaction product; S13: cooling the first reaction product to room temperature, and sequentially performing precipitation centrifugal washing and vacuum drying to obtain copper vanadate.
[0051] The method comprises dispersing and dissolving vanadium pentoxide, hydrogen peroxide and copper nitrate trihydrate in water to ensure that the three are evenly mixed; stirring the mixed solution to ensure that the mixed solution is stirred more evenly and improve the subsequent reaction efficiency; and performing a hydrothermal reaction on the mixed solution in a reactor to obtain a first reaction product. The reaction method has the characteristics of simple operation, low cost and excellent performance of the synthesized nanocrystals. The first reaction product is cooled to room temperature to obtain a crystalline substance, and then centrifugal washing and vacuum drying are performed in sequence to remove impurities on the surface of the crystal, and finally copper vanadate is obtained.
[0052] Preferably, the concentration of hydrogen peroxide may range from 25wt.% to 35wt.%, and more preferably from 30wt.%. The water used for dispersing and dissolving vanadium pentoxide, hydrogen peroxide and copper nitrate trihydrate may be deionized water to reduce the generation of impurities. Preferably, the mixed solution is stirred at a temperature of 25°C to 60°C to ensure that the mixed solution is stirred more evenly and to improve the reaction efficiency of the hydrothermal reaction.
[0053] In some embodiments of the present application, in S12, the temperature of the hydrothermal reaction is ≥150°C; and / or the time of the hydrothermal reaction is 12h-96h.
[0054] The appropriate hydrothermal reaction temperature can ensure that Cu 2+ All of them enter the vanadium oxide interlayer to form Cu-BTA molecules, and then Cu-BTA provides support for the interlayer, thereby improving the rate performance and cycle performance; the evenly stirred mixed solution is placed in a reactor for hydrothermal reaction, and the hydrothermal reaction time is controlled within 12h-96h to ensure that the mixed solution reacts more fully.
[0055] In some embodiments of the present application, the stirring time is 10 min-60 min; and / or the temperature of the hydrothermal reaction is 200°C-250°C; and / or the cleaning solvent for the precipitation centrifugal cleaning includes deionized water and anhydrous ethanol; and / or the temperature of vacuum drying is 60°C-100°C; and / or the time of vacuum drying is 3h-48h.
[0056] The mixed solution is stirred at 25°C-60°C, and the stirring time is controlled within 10min-60min to promote the mixing of the mixed solution more evenly, which is convenient for the subsequent hydrothermal reaction; the mixed solution is placed in a reactor for hydrothermal reaction, and the temperature of the hydrothermal reaction is controlled within 200°C-250°C. The appropriate hydrothermal reaction temperature can promote the Cu 2+ All of them enter the vanadium oxide interlayer to form Cu-BTA molecules, thereby ensuring that Cu-BTA provides support for the interlayer, thereby improving the rate performance and cycle performance; the cleaning solvents for precipitation centrifugal cleaning include deionized water and anhydrous ethanol, each centrifugal cleaning is performed 3 times, and deionized water and anhydrous ethanol are used alternately for cleaning. The cleaning process can control the centrifugal speed to improve the cleaning efficiency; when the first reaction product is cleaned, it is vacuum dried, the vacuum drying temperature is 60℃-100℃, and the vacuum drying time is 3h-48h, and finally the required copper vanadate is obtained.
[0057] Preferably, the stirring time is 25 min-45 min; the temperature of the hydrothermal reaction is 180° C.-220° C.; the time of the hydrothermal reaction is 30 h-78 h; the temperature of the vacuum drying is 70° C.-90° C.; and the time of the vacuum drying is 12 h-35 h.
[0058] In some embodiments of the present application, S20 specifically includes: S21: dissolving 1,2,4,5-benzenetetraamine tetrahydrochloride in water to obtain a 1,2,4,5-benzenetetraamine tetrahydrochloride solution; S22: adding the 1,2,4,5-benzenetetraamine tetrahydrochloride solution to the copper vanadate dispersion under stirring conditions, slowly adding an ammonia solution thereto after stirring evenly, and then transferring it to a constant temperature water bath and stirring for reaction to obtain a second reaction product; S23: centrifugally cleaning and vacuum drying the second reaction product in sequence to obtain a positive electrode material.
[0059] Dissolving 1,2,4,5-benzenetetraamine tetrahydrochloride in water can promote the reaction of the two and make the reaction more complete; stirring the reaction in a constant temperature water bath can not only make the reaction more uniform, but also ensure the stability of heating, which is conducive to the reaction; the second reaction product is centrifugally cleaned and vacuum dried in turn to remove impurities on the crystal surface, and finally the positive electrode material is obtained.
[0060] Among them, the addition of ammonia solution can deprotonate 1,2,4,5-benzenetetraamine tetrahydrochloride, thereby reacting with the Cu between the vanadium oxide layers. 2+ For coordination, preferably, the concentration range of the ammonia solution can be 23wt.%-33wt.%, and more preferably 28wt.%. It should also be noted that the water used for dispersing the copper vanadate and the water used for dissolving 1,2,4,5-benzenetetraamine tetrahydrochloride can be deionized water to avoid the generation of other impurities.
[0061] In some embodiments of the present application, the stirring speed is 100r / min-400r / min; and / or the reaction time is 3h-48h; and / or the cleaning solvent for centrifugal cleaning includes deionized water and acetone; and / or the vacuum drying temperature is 60℃-100℃; and / or the vacuum drying time is 12h-96h.
[0062] The reactants are placed in a constant temperature water bath and stirred for reaction, and the stirring speed is controlled to be 100r / min-400r / min. By controlling the appropriate stirring speed, the diffusion of BTA molecules into the interlayer of vanadium oxide is promoted to improve the rate performance and cycle performance of the positive electrode material. The reaction time of 1,2,4,5-benzenetetraamine tetrahydrochloride and copper vanadate is controlled to be 3h-48h to ensure a more complete reaction; the cleaning solvents for centrifugal cleaning include deionized water and acetone, and each is centrifuged for 3 times; after the second reaction product is cleaned, it needs to be vacuum dried, the vacuum drying temperature is 60℃-100℃, and the vacuum drying time is 12h-96h, and finally the desired positive electrode material is obtained.
[0063] Preferably, the speed of magnetic stirring is 180 r / min-320 r / min; the reaction time is 3 h-48 h; the temperature of vacuum drying is 70° C.-90° C.; and the vacuum drying time is 30 h-78 h.
[0064] An embodiment of the present invention further provides a zinc ion battery, comprising the positive electrode material as described above. The zinc ion battery has the same beneficial effects as the positive electrode material as described above, so it will not be described in detail here.
[0065] Example 1 This embodiment provides a method for preparing a positive electrode material, comprising the following steps: S1: Add 0.6g of vanadium pentoxide to 60ml of deionized water, then measure 8ml of 30wt.% hydrogen peroxide solution, and slowly drop it into the above dispersion under magnetic stirring. After the dropwise addition is completed, continue stirring for 30min at a water bath temperature of 40°C. Then add 159.4mg of copper nitrate trihydrate and stir evenly. Then transfer the mixed solution obtained above to a hydrothermal reactor with a capacity of 100mL, react at a temperature of 200°C for 48h to obtain the first reaction product. After the reaction is completed, the first reaction product is centrifuged and washed 3 times with deionized water and anhydrous ethanol, and then the precipitate is placed in a vacuum drying oven at a temperature of 60°C and dried for 12h, and ground into powder to obtain copper vanadate.
[0066] S2: Weigh 97.3 mg of copper vanadate in step S1 and disperse it in 5 ml of deionized water. At the same time, weigh 28.4 mg of 1,2,4,5-benzenetetraamine tetrahydrochloride and dissolve it in 5 ml of deionized water. Then, add the 1,2,4,5-benzenetetraamine tetrahydrochloride solution dropwise to the copper vanadate dispersion under stirring conditions. After the two are evenly mixed, add 20 μL of 28 wt.% ammonia solution. Then transfer the mixed solution to a 30 ml screw-on glass bottle, maintain magnetic stirring at a speed of 200 r / min for 24 hours, and react to obtain the second reaction product. The second reaction product is centrifuged and washed 3 times with deionized water and acetone respectively, and then the precipitate is placed in a vacuum drying oven at a temperature of 80°C and dried for 24 hours to obtain the positive electrode material, whose chemical formula is (Cu-BTA) 0.2 V 2 O 5 .
[0067] Among them, the positive electrode material (Cu-BTA) x V 2 O 5 The insertion amount of the conductive metal organic framework can be characterized by ICP detection of Cu ion content.
[0068] The morphology of the positive electrode material provided in this embodiment 1 is shown in Figure 1 , the length of the nanosheet is 80nm-200nm and the thickness is 3nm-7nm.
[0069] Vanadium-based positive electrode material (Cu-BTA) prepared in this example 0.2 V 2 O 5 The XRD diffraction pattern of Figure 2 As shown in the figure, the vanadium-based cathode material shows an obvious (001) diffraction peak, corresponding to a layered structure. According to the Bragg equation, it has a large interlayer spacing (1.39 nm).
[0070] from Figure 2 As shown in the XRD diffraction pattern, the diffraction peak at about 18° is the diffraction peak of Cu-BTA, that is, Cu and BTA form a coordination structure.
[0071] Assembly and testing of aqueous zinc ion batteries: Take the (Cu-BTA) obtained in this example 0.2 V 2 O 5The electrode sheet was prepared by mixing Ketjen black and 60% polytetrafluoroethylene dispersion in a mass ratio of 70:20:10 and dispersing the mixture in ethanol. The mixture was then rolled into a film and dried in a vacuum oven at 60°C for 12 hours. The film was then pressed onto a stainless steel mesh to obtain an electrode sheet. The electrode sheet, metal sheet, Whatman glass fiber membrane (GF / F) and 3M zinc trifluoromethanesulfonate (Zn(CF 3 SO 3 ) 2 ) aqueous solution as the working electrode (positive electrode), counter electrode, diaphragm and electrolyte, and assembled into a 2032-type button cell in air. The constant current charge and discharge test of the battery uses a LANDCT2001A tester with a cut-off voltage of 0.3V-1.4V.
[0072] Example 2 This embodiment provides a method for preparing a positive electrode material. The specific steps are as in Example 1, except that the mass of copper nitrate trihydrate weighed in S1 is 79.7 mg, and the mass of copper vanadate weighed in S2 is 188.2 mg. The chemical formula of the prepared positive electrode material is (Cu-BTA) 0.1 V 2 O 5 , the interlayer spacing of vanadium oxide is 1.30nm.
[0073] Example 3 This embodiment provides a method for preparing a positive electrode material. The specific steps are as in Example 1, except that the mass of copper nitrate trihydrate weighed in S1 is 239.1 mg, and the mass of copper vanadate weighed in S2 is 76.7 mg. The chemical formula of the prepared positive electrode material is (Cu-BTA) 0.3 V 2 O 5 , the interlayer spacing of vanadium oxide is 1.45nm.
[0074] Example 4 This embodiment provides a method for preparing a positive electrode material. The specific steps are as in Example 1, except that 10 ml of 30 wt.% hydrogen peroxide solution is measured in S1, the stirring temperature is 60°C, the stirring time is 10 min, the hydrothermal temperature is 250°C, the reaction time is 12 h, the drying temperature is 100°C, and the drying time is 3 h; the speed of magnetic stirring in S2 is 400 r / min, the reaction time is 3 h, the drying temperature is 60°C, and the drying time is 96 h. The chemical formula of the prepared positive electrode material is (Cu-BTA) 0.18 V 2 O 5 , the interlayer spacing of vanadium oxide is 1.36nm.
[0075] Example 5 This embodiment provides a method for preparing a positive electrode material. The specific steps are as in Example 1, except that 10 ml of 30 wt.% hydrogen peroxide solution is measured in S1, the stirring temperature is 25°C, the stirring time is 60 min, the hydrothermal temperature is 150°C, the reaction time is 96 h, the drying temperature is 60°C, and the drying time is 48 h. In S2, the magnetic stirring speed is 100 r / min, the reaction time is 48 h, the drying temperature is 100°C, and the drying time is 12 h. The chemical formula of the prepared positive electrode material is (Cu-BTA) 0.14 V 2 O 5 , the interlayer spacing of vanadium oxide is 1.32nm.
[0076] Example 6 This embodiment provides a method for preparing a positive electrode material. The specific steps are as in Embodiment 1, except that the hydrothermal temperature in S1 is 180°C. The chemical formula of the prepared positive electrode material is (Cu-BTA) 0.2 V 2 O 5 , the interlayer spacing of vanadium oxide is 1.20nm.
[0077] Comparative Example 1 This comparative example provides a method for preparing a positive electrode material. The specific steps are as shown in Example 1, except that step S2 is not performed in this comparative example. 0.2 V 2 O 5 The XRD diffraction pattern of Figure 3 As shown, the vanadium-based cathode material shows a (001) diffraction peak, corresponding to a layered structure. According to the Bragg equation, its interlayer spacing is 1.17 nm.
[0078] Comparative Example 2 This comparative example provides a method for preparing a positive electrode material. The specific steps are as in Example 1, except that the mass of copper nitrate trihydrate weighed in S1 is 39.9 mg, and the mass of copper vanadate weighed in S2 is 389.2 mg. The chemical formula of the prepared positive electrode material is (Cu-BTA) 0.05 V 2 O 5 , the interlayer spacing of vanadium oxide is 1.24nm.
[0079] Comparative Example 3 This comparative example provides a method for preparing a positive electrode material. The specific steps are as in Example 1, except that the mass of copper nitrate trihydrate weighed in S1 is 318.8 mg, and the mass of copper vanadate weighed in S2 is 48.65 mg. The chemical formula of the prepared positive electrode material is (Cu-BTA) 0.4 V2 O 5 , the interlayer spacing of vanadium oxide is 1.56nm.
[0080] The positive electrode materials obtained according to Examples 1-6 and Comparative Examples 1-3 were assembled and their electrochemical properties were tested according to the assembly and testing method of the aqueous zinc ion battery described in Example 1. The test results are shown in Table 1.
[0081] Table 1: Electrochemical performance of different samples From the comparison between Comparative Example 1 and Example 1, it can be seen that pre-embedding an appropriate Cu-BTA conductive metal organic framework between vanadium oxide layers has a better effect than only embedding Cu 2+ In terms of the specific capacity, rate performance and cycle performance of vanadium oxide, it is beneficial to improve the specific capacity, rate performance and cycle performance of vanadium oxide. In addition, the interlayer spacing of vanadium oxide in comparative example 1 is smaller than that of vanadium oxide in example 1. This is because the conductive metal organic framework itself is larger, which can expand the interlayer spacing of vanadium oxide to a greater extent, thereby improving the capacity of example 1. Furthermore, the (001) diffraction peak in the XRD of example 1 shifts to a low angle, indicating that the interplanar spacing increases, which can prove that the conductive metal organic framework is embedded between the layered structures of vanadium oxide.
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode material, characterized in that: It comprises a conductive metal organic framework and vanadium oxide; the conductive metal organic framework is embedded between the layered structures of the vanadium oxide; The chemical formula of the positive electrode material is (Cu-BTA) x V2O5; Wherein, 0.10≤x≤0.30, BTA is 1,2,4,5-benzenetetramine, and Cu-BTA is the conductive metal organic framework.
2. The positive electrode material according to claim 1, characterized in that The structure of the positive electrode material is in the form of nanosheets, the length of the nanosheets is 80nm-200nm, and the thickness of the nanosheets is 3nm-7nm.
3. The positive electrode material according to claim 1, characterized in that The interlayer distance of the vanadium oxide is 1.30nm-1.45nm.
4. A method for preparing a positive electrode material, characterized in that: The preparation method is used to prepare the positive electrode material according to any one of claims 1 to 3, and the preparation method comprises the following steps: S10: dispersing and dissolving vanadium pentoxide, hydrogen peroxide, copper nitrate trihydrate and water in a mass ratio of 1: (4-6): (0.13-0.40): (80-120), and then performing a hydrothermal reaction to obtain copper vanadate; S20: dispersing the copper vanadate in water to form a copper vanadate dispersion, adding a 1,2,4,5-benzenetetraamine tetrahydrochloride solution to the copper vanadate dispersion, and then adding an ammonia solution thereto and stirring to react; the mass ratio of 1,2,4,5-benzenetetraamine tetrahydrochloride in the 1,2,4,5-benzenetetraamine tetrahydrochloride solution, the copper vanadate in the copper vanadate dispersion, and the ammonia source in the ammonia solution is 1: (2.70-6.63): (0.15-0.25); obtaining the positive electrode material.
5. The preparation method according to claim 4, characterized in that: S10 specifically includes: S11: dispersing and dissolving the vanadium pentoxide, the hydrogen peroxide and the copper nitrate trihydrate in water to obtain a mixed solution; S12: After the mixed solution is stirred evenly, it is transferred to a reaction kettle for hydrothermal reaction to obtain a first reaction product; S13: Cooling the first reaction product to room temperature, performing centrifugal washing and vacuum drying on the precipitate to obtain the copper vanadate.
6. The preparation method according to claim 5, characterized in that: In S12, the temperature of the hydrothermal reaction is ≥150° C.; and / or the time of the hydrothermal reaction is 12 h-96 h.
7. The preparation method according to claim 5, characterized in that: The stirring time is 10min-60min; and / or The temperature of the hydrothermal reaction is 200°C-250°C; and / or The cleaning solvent for the centrifugal cleaning of the precipitate comprises deionized water and anhydrous ethanol; and / or The vacuum drying temperature is 60°C-100°C; and / or The vacuum drying time is 3h-48h.
8. The preparation method according to claim 4, characterized in that: S20 specifically includes: S21: dissolving 1,2,4,5-benzenetetramine tetrahydrochloride in water to obtain the 1,2,4,5-benzenetetramine tetrahydrochloride solution; S22: adding the 1,2,4,5-benzenetetraamine tetrahydrochloride solution to the copper vanadate dispersion under stirring, adding the ammonia solution thereto after stirring evenly, and then transferring the mixture to a constant temperature water bath and stirring to react, thereby obtaining a second reaction product; S23: centrifugally washing and vacuum drying the second reaction product in sequence to obtain the positive electrode material.
9. The preparation method according to claim 8, characterized in that: The stirring speed is 100r / min-400r / min; and / or The reaction time is 3h-48h; and / or The cleaning solvent of the centrifugal cleaning comprises deionized water and acetone; and / or The vacuum drying temperature is 60°C-100°C; and / or The vacuum drying time is 12h-96h.
10. A zinc ion battery, characterized in that: The method comprises the positive electrode material as described in any one of claims 1 to 3.